Is AI Widening Healthcare Disparities? A Critical Examination of Algorithmic Bias and Health Equity - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Is AI Widening Healthcare Disparities? A Critical Examination of Algorithmic Bias and Health Equity The integration of Artificial Intelligence (AI) into...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine